1960
DOI: 10.1677/joe.0.0210263
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Steroid Excretion in Three Types of Post-Pubertal Hirsutism

Abstract: The steroid excretion of patients with three types of post-pubertal hirsutism has been studied both before and during the administration of corticotrophin. The types of hirsutism distinguished were post-pubertal adrenal virilism (three cases), idiopathic hirsutism (five cases) and the Stein-Leventhal syndrome (seven cases).1. The patients in the adrenal virilism group were found to have a pattern of steroid excretion of the type seen in congenital adrenal hyperplasia. Thus they excreted relatively small amount… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
14
0

Year Published

1961
1961
1987
1987

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 5 publications
2
14
0
Order By: Relevance
“…Patients with the postpubertal form of congenital adrenal hyperplasia excrete increased quantities of urinary 17-ketosteroids and manifest virilism (3). While neither of these criteria was fulfilled in any of our patients, their urinary pregnanediol and pregnanetriol excretion was not studied..…”
Section: Methodsmentioning
confidence: 71%
See 2 more Smart Citations
“…Patients with the postpubertal form of congenital adrenal hyperplasia excrete increased quantities of urinary 17-ketosteroids and manifest virilism (3). While neither of these criteria was fulfilled in any of our patients, their urinary pregnanediol and pregnanetriol excretion was not studied..…”
Section: Methodsmentioning
confidence: 71%
“…These were 10 consecutive women, referred to us with primary complaints of hypertrichosis; their mean age was (1,3), these patients were chosen only if their total 17-ketosteroid and corticoid excretion in a 24-hour urine specimen was within normal range. Adult hirsutism may be a manifestation of ovarian neoplasms and Cushing's syndrome and is associated with the postpubertal analog of congenital adrenal hyperplasia, and the Stein-Leventhal syndrome (3,15). It is most unlikely that the patients studied here represented hirsutism secondary to ovarian neoplasia or Cushing's syndrome, since they were selected from a clinical population in which either of these two disease entities is extremely rare.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the patients classified as having "idiopathic hirsutism" (7)(8)(9)(10)(11)(12)(13)(14)(15)(16) had menstrual abnormalities, but none of this group had enlarged ovaries. A 24-hour urine specimen served as a control in each patient studied.…”
Section: Methodsmentioning
confidence: 99%
“…The second abnormality is an increased urinary level of androsterone and etiocholanolone. In the latter instance some authors have suggested that the adrenal is responsible for the precursors of the increased androsterone and etiocholanolone (3)(4)(5)(6)(7), although others have suggested an ovarian origin and still others could not discern the glandular origin of these steroids (8)(9)(10). A significant residual level of urinary 17KS after adrenal suppression following administration of analogs of cortisol (11)(12)(13)(14)(15) favors an ovarian origin of the precursors responsible for the elevation of the androsterone and etiocholanolone values reported.…”
mentioning
confidence: 99%